Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Lê Ngọc Bảo Ngân
Nguyễn Lê Phước Thịnh
7 tháng 12 2023 lúc 20:29

Bài 2:

a: ĐKXĐ: \(x\ne-2\)

b: \(D=\dfrac{2x^2-4x+8}{x^3+8}\)

\(=\dfrac{2\left(x^2-2x+4\right)}{\left(x+2\right)\left(x^2-2x+4\right)}\)

\(=\dfrac{2}{x+2}\)

c: Khi x=2 thì \(D=\dfrac{2}{2+2}=\dfrac{2}{4}=\dfrac{1}{2}\)

Bài 1:

a: ĐKXĐ: \(x\notin\left\{-3;2\right\}\)

b: \(A=\dfrac{x+2}{x+3}-\dfrac{5}{x^2+x-6}+\dfrac{1}{2-x}\)

\(=\dfrac{x+2}{x+3}-\dfrac{5}{\left(x+3\right)\left(x-2\right)}-\dfrac{1}{x-2}\)

\(=\dfrac{\left(x+2\right)\left(x-2\right)-5-x-3}{\left(x-2\right)\left(x+3\right)}\)

\(=\dfrac{x^2-4-x-8}{\left(x-2\right)\left(x+3\right)}\)

\(=\dfrac{x^2-x-12}{\left(x-2\right)\left(x+3\right)}=\dfrac{\left(x-4\right)\left(x+3\right)}{\left(x-2\right)\left(x+3\right)}=\dfrac{x-4}{x-2}\)

c: A=-3/4

=>\(\dfrac{x-4}{x-2}=\dfrac{-3}{4}\)

=>\(4\left(x-4\right)=-3\left(x-2\right)\)

=>4x-16=-3x+6

=>4x+3x=16+6

=>7x=22

=>\(x=\dfrac{22}{7}\left(nhận\right)\)